Proper Motion and Secular Variations of Keplerian Orbital Elements - Butkevich, Alexey G. (Frontiers in Astronomy and Space Sciences, 2018)
High-precision observations require accurate modeling of secular changes in the orbital elements in order to extrapolate measurements over long time intervals, and to detect deviation from pure Keplerian motion caused, for example, by other bodies or relativistic effects. We consider the evolution of the Keplerian elements resulting from the gradual change of the apparent orbit orientation due to proper motion. We present rigorous formulae for the transformation of the orbit inclination, longitude of the ascending node and argument of the pericenter from one epoch to another, assuming uniform stellar motion and taking radial velocity into account. An approximate treatment, accurate to the second-order terms in time, is also given. The proper motion effects may be significant for long-period transiting planets. These theoretical results are applicable to the modeling of planetary transits and precise Doppler measurements as well as analysis of pulsar and eclipsing binary timing observations.